Focjusz a kuchnia grecka, czyli kilka słów o abyrtake (abyptakh) - Kokoszko, Maciej; Gibel, Katarzyna (Vox Patrum, 2008)
The present commentary is aimed at elucidating the terms made use of by Photius, the Patriarch of Constantinople, in the entry abyrtake included in his Lexicon. The authors of the study maintain that abyrtake was a sauce of Medic (i.e. Persian) origin, which might have been known to the Greeks even before the VIth century but eventually beeame popular in the IVth, BC. It was a luxury dish eonsisting of vinegar, eress, garlic, mustard, raisins and salted capers.